A new species of forest-dwelling Cyrtodactylus Gray (Squamata: Gekkonidae) from the Indawgyi Wildlife Sanctuary, Kachin State, Myanmar - Grismer, L. Lee; Wood, Perry L. Jr.; Quah, Evan S. H.; Thura, Myint Kyaw; Herr, Mark W.; Lin, Aung Ko (Zootaxa, 2019)
A herpetological survey of the Indawgyi Wildlife Sanctuary in Kachin State, Myanmar resulted in the discovery of a new species of Cyrtodactylus Gray along the eastern watershed of the Mokso Mountains. An integrative taxonomic analysis based on the mitochondrial ND2 gene, morphology, and color pattern recovered this new species, Cyrtodactylus mombergi sp. nov., as the sister taxon to an undescribed species from Miao, Arunachal Pradesh, India. Bayesian and maximum likelihood analyses recovered notable genetically divergent (4.7%) phylogeographic structure between northern and southern populations of C. mombergi sp. nov. across only 14 km of continuous habitat. Conversely, genetic divergence did not exceed 9.2% between C. mombergi sp. nov. and the undescribed species from Miao from across 355 km of habitat. Cyrtodactylus mombergi sp. nov. belongs to a well-supported, mitochondrial clade of 18 other species which now compose an expanded and redefined C. gansi group. Cyrtodactylus mombergi sp. nov. is only the third species of Bent-toed Gecko reported from Kachin State and indicates that additional herpetological surveys are needed in unexplored forested areas.